2019
DOI: 10.1017/s1365100519000622
|View full text |Cite
|
Sign up to set email alerts
|

Inflation and Growth: A Non-Monotonic Relationship in an Innovation-Driven Economy

Abstract: This paper investigates the effects of monetary policy on long-run economic growth via different cash-in-advance (CIA) constraints on R&D in a Schumpeterian growth model with vertical and horizontal innovations. The relationship between inflation and growth is contingent on the relative extents of CIA constraints and diminishing returns to two types of innovation. This model can generate a mixed (monotonic or non-monotonic) relationship between inflation and growth, given that the relative strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 65 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…The discount rate ρ is set to a conventional value of 0.02. As for the strength of the CIA constraint on consumption (i.e., ξ), we follow Zheng et al (2019) to set it to 0.17, for matching the ratio of M1-consumption in the US. As for the strength of the CIA constraint on manufacturing, we follow Arawatari et al (2018) to set α = 1 as the benchmark.…”
Section: Quantitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The discount rate ρ is set to a conventional value of 0.02. As for the strength of the CIA constraint on consumption (i.e., ξ), we follow Zheng et al (2019) to set it to 0.17, for matching the ratio of M1-consumption in the US. As for the strength of the CIA constraint on manufacturing, we follow Arawatari et al (2018) to set α = 1 as the benchmark.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…A noticeable representative along this line of effort is the pioneering work of Marquis and Reffett (1994), which explores the effects of inflation on growth in the framework of Romer (1990). 2 A great number of studies have analyzed the effects of inflation in a Schumpeterian quality-ladder model, such as Chu and Lai (2013), Chu and Cozzi (2014), Chu et al (2015), Chu and Ji (2016), Huang et al (2017), Oikawa and Ueda (2018), Zheng et al (2019), Huang et al (2019), andGil andIglésias (2020). These models, however, all feature an identical step size of quality improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The inflation rate variability, black market premium, and interest rate variability are widely used proxies for macroeconomic conditions. Existing studies have shown that poor macroeconomic conditions, as measured by these indicators, disincentivize economic actors from engaging in productive economic activities or reaping the benefits thereof (Kandil 1992;Ćorić and Pugh 2010;Zheng et al 2021). It also prevents the economy from adjusting effectively to technological change.…”
Section: Gvc and Productive Efficiency: The Role Of Country Character...mentioning
confidence: 99%
“…which is now decreasing in the nominal interest rate 𝑖 only via the CIA constraint on R&D investment (i.e., 𝛽 > 0). Huang et al (2021) and Zheng et al (2021) also consider the second-generation Schumpeterian growth model and confirm that an increase in the nominal interest rate has a negative effect on economic growth via the CIA constraint on quality-improving R&D. Interestingly, they find that an increase in the nominal interest rate has a positive effect on economic growth via a CIA constraint on variety-expanding R&D. The intuition of this result can be seen from ( 21), which shows that a smaller number of products 𝑁 gives rise to a higher growth rate 𝑔 = 𝜆 ln 𝑧 by increasing the amount of resources for the innovation of each product. 7…”
Section: Proposition 1 An Increase In the Nominal Interest Rate Reduc...mentioning
confidence: 99%